2014
DOI: 10.4103/2278-0203.143233
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic bracket designs and their impact on microbial profile and periodontal disease: A clinical trial

Abstract: Aim:The aim of the present study was to compare the undisturbed plaque formation on teeth bonded with Preadjusted (Captain Ortho, Libral Traders, Mumbai, India) and Begg Brackets (Captain Ortho, Libral Traders, Mumbai, India) with nonbonded control sites via a de novo plaque growth over a period of 7 days.Materials and Methods:A clinical trial with the split-mouth design was set up enrolling 10 dental students. Within each subject sites with (Preadjusted) (P-site), Begg brackets (B-site) and control sites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
15
0
4
Order By: Relevance
“…Traditional fixed appliances, whether of single or twin design, produce stagnation zones which produce a challenge to mechanical plaque control. Bracket design influences both caries risk and periodontal parameters . In addition, retention of plaque is also affected by the surface roughness of the appliance, and the type of ligatures used.…”
Section: Appliance Typementioning
confidence: 99%
“…Traditional fixed appliances, whether of single or twin design, produce stagnation zones which produce a challenge to mechanical plaque control. Bracket design influences both caries risk and periodontal parameters . In addition, retention of plaque is also affected by the surface roughness of the appliance, and the type of ligatures used.…”
Section: Appliance Typementioning
confidence: 99%
“…The zones around the fixed braces are preelection areas for the accumulation of a larger amount of dental plaque. All this predisposes to decrease the pH in the dental biofilm and in the presence of carbohydrates in patient`s diet, a physical barrier is formed that disturbs remineralization with the calcium and phosphate ions from the saliva (7,8). All these changes in the oral ecosystem help to increase the levels of S. mutans and Lactobacillus spp., mainly around the adhesives that fix the orthodontic appliances (9).…”
Section: Discussionmentioning
confidence: 99%
“…Galimanas et al (2014) suggested using salivary bacteria abundance ratios as a means for differentiating between healthy and diseased patients (34). Taxonomic ratios have been used to differentiate between subjects in studies of obesity (35), diabetes (36), and periodontal disease (37). Ratio comparisons also help to control for high levels of taxonomic variability among individuals (38)(39)(40)(41).…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%